Cover Feature: Exploring the Corundum Structure as a Host for Colored Compounds – Synthesis, Structures, and Optical Studies of (MM′)3TeO6 (M = Mg, Mn, Co, Ni, Zn; M′ = Mg, Mn, Co, Ni, Cu) (Eur. J. Inorg. Chem. 20‐21/2018). Issue 20 (1st June 2018) - Bhim, Anupam; Gopalakrishnan, Jagannatha; Natarajan, Srinivasan
Abstract : The Cover Feature shows the different colors obtained by suitably substituting transition elements in the distorted octahedral environment within the corundum‐derived structures. More information can be found in theFull Paper by A. Bhim, J. Gopalakrishnan, and S. Natarajan .